The Role of Learning Media in Developing English Semantic Understanding - Sintania (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
Semantic comprehension, or the ability to understand words and sentences in the right context, is an important component that allows students to better interpret texts. The development of technology has encouraged the use of more innovative learning media to make education more interesting. Learning media can include various forms, such as printed materials, videos, interactive applications, and e-learning platforms, and can increase student motivation and engagement. This study examines the role of learning media in improving semantic understanding of English. This study collected data through surveys, interviews, and classroom observations. The purpose of this study was to find patterns and trends in the use of learning media, as well as the impact of using these media on students' semantic understanding. This evaluation includes an analysis of the advantages and disadvantages of various types of media, as well as the best methods for integrating media into learning. The results of the study are expected to provide practical, evidence-based advice on how to use learning media in teaching English. The purpose of this study is to improve English language education in schools so that students are better prepared to face challenges around the world.